3D structure of three jumbo phage heads. (25th November 2020) - Neumann, Emmanuelle; Kawasaki, Takeru; Effantin, Grégory; Estrozi, Leandro F.; Chatchawankanphanich, Orawan; Yamada, Takashi; Schoehn, Guy
Abstract : Jumbo phages are bacteriophages that carry more than 200 kbp of DNA. In this study we characterized two jumbo phages (ΦRSL2 and ΦXacN1) and one semi-jumbo phage (ΦRP13) at the structural level by cryo-electron microscopy. Focusing on their capsids, three-dimensional structures of the heads at resolutions ranging from 16 to 9 Å were calculated. Based on these structures we determined the geometrical basis on which the icosahedral capsids of these phages are constructed, which includes the accessory and decorative proteins that complement them. A triangulation number novel to Myoviridae (ΦRP13; T =21) was discovered as well as two others, which are more common for jumbo phages ( T =27 and T =28). Based on one of the structures we also provide evidence that accessory or decorative proteins are not a prerequisite for maintaining the structural integrity of very large capsids.